Clinical Analysis on Alteration of Thyroid Hormones in the Serum of Patients with Acute Ischemic Stroke. (28th July 2010) - Zhang, Yonghua; Meyer, Michael A.
Abstract : Low T3 has been associated with increased short-term mortality in intensive care unit and long-term mortality in cardiovascular disease. The objective of this retrospective study is to investigate associations of thyroid hormone status with clinical severity and outcome in acute ischemic stroke, and whether there is association between the pituitary axis abnormality and the anterior/posterior circulation involvement. Patients with no history of thyroid abnormality who presented first ever stroke were studied. Total T3, T4, TSH levels, basic and clinical characteristics were collected and categorized. Neurological impairment was assessed using NIHSS and modified Rankin Scale. Twenty-nine patients (61%) had T3≤ 75 ng/dL. Low T3 group had significant higher NIHSS compared to normal T3 group. There was a significant negative correlation between T3 levels and NIHSS scores on admission. A significantly smaller percentage of patients with low T3 showed favorable neurological function improvement by both NIHSS and mRS measures compared to those with normal T3. There was no significant difference for anterior or posterior circulation involvement between low T3 and normal T3 groups. It is suggested that low T3 is associated with worse neurological outcome. The severity of low T3 may be a predictor of functional improvement in acute ischemic stroke.